Technology-Based Administration Management in Supporting Teachers’ Careers at MA Miftahul Qulub Polagan Pamekasan - Moh. Badruddin Amin; Sitti Mahbubah; Abdul Wafi (Pusdikra-Publishing.com, 2023)
Administration management is very important for educational institutions because the administration is useful for data management in achieving a goal. This research originated from the researcher's interest in knowing technology-based administration in supporting teachers’ careers. This study aims 1) to know the planning of technology-based administrative management in supporting teachers’ careers at MA Miftahul Qulub Polagan Pamekasan. 2) to know the use of technology-based administration in supporting teachers’ careers at MA Miftahul Qulub Polagan Pamekasan. 3) to know the advantages and disadvantages of administration management in supporting teachers’ careers at MA Miftahul Qulub Polagan Pamekasan. To achieve the above objectives, this study uses a qualitative approach with a type of descriptive research. In data collection, this study used observation (non-participants), interviews (semi-structured) to the parties concerned and documentation. As for data analysis, researcher carrie out three stages, namely by reducing the data then displaying the data in the form of a brief description and drawing conclusions.